2017
DOI: 10.1099/jmm.0.000505
|View full text |Cite
|
Sign up to set email alerts
|

Candidaemia in a tertiary care academic hospital in Italy. The impact of C. parapsilosis complex on the species distribution and antifungal susceptibility

Abstract: Purpose. To analyse the species distribution and the susceptibility profiles to the major antifungal agents of Candida isolated from bloodstream infections (BSIs) in both intensive care units (ICUs) and non-ICU wards in a tertiary care hospital in Italy from 2010 until 2015.Methodology. Episodes of Candida BSI were recorded in a retrospective observational cohort study. Yeasts were isolated from both blood and intravascuIar devices (IVDs) and their susceptibility to antifungal drugs was tested using the microd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…In total, we included 107 studies in our analysis. [13][14][15][16][18][19][20][21][22]25,26,34,36,37, Fifty [13][14][15][16]22,37,52,[114][115][116]120,121,126,128,129,133,136 of 107 studies [13][14][15][16][18][19][20][21][22]25,26,34,36,37, were teaching hospital-based, 18 were populationbased, [20][21][22]25,26,34,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, we included 107 studies in our analysis. [13][14][15][16][18][19][20][21][22]25,26,34,36,37, Fifty [13][14][15][16]22,37,52,[114][115][116]120,121,126,128,129,133,136 of 107 studies [13][14][15][16][18][19][20][21][22]25,26,34,36,37, were teaching hospital-based, 18 were populationbased, [20][21][22]25,26,34,…”
Section: Resultsmentioning
confidence: 99%
“…Pooled analysis indicated that studies with a study median between 2001 and 2010 had a higher IR with 1.11 (95% CI 0.83-1.39) [13][14][15][16]55,60,61,63,66,71,[73][74][75]81,136 compared to studies with a study median between 1990 and 2000 with 0.62 (95% CI 0.41-0.83), 22,77,79,[82][83][84][85] and studies with a study median between 2011 and now with 0.97 (95% CI 0.56-1.39) ( Figure 3) (p-value for interaction <0.001). 52,[56][57][58][59]62,114,115,120 Studies from southern European countries had a higher pooled IR (1.13, 95% CI 0.9-1.35) 13,14,16,52,[56][57][58][60][61][62][63]66,71,[73][74]…”
Section: Hospital-based Incidence Of Candidaemia In Europementioning
confidence: 99%
See 1 more Smart Citation
“…A pathobiont is a microorganism which, despite expressing attributes of virulence, nevertheless continues to live in symbiosis with the host, and therefore does not cause a clinically verifiable lesion [78]. This is possible as long as the Th1-Th2-Th17-Treg balance remains intact, and fundamentally it will depend on a good Th17 response, since recent evidences show that this response is crucial for antifungal mucous defense; especially in oral mucosa [78,79]. When such balance breaks down, the clinical result could be oral candidiasis or invasive candidiasis.…”
Section: Oral Mucosa As a Potential Source Of Candidemia By Candida Pmentioning
confidence: 99%
“…The advantage of this research is that for the candidemia model by Candida parapsilosis, the skin of fingers, would not be the only route of infection as the international consensus raises [1], but for everything developed in this review, we consider that the mouth would also be a possible route of infection in candidemia by this species of Candida, and even more if the oral cavity is in inflammatory conditions determined by gingivo-periodontal disease. This is particularly important from recent retrospective cohort studies, which show a significant increase in the incidence of candidemia by Candida species not Candida albicans, with Candida parapsilosis sensu stricto being the protagonist; and even more so when it is demonstrated that the morbidity and mortality due to nosocomial candidemia in preterm infants is higher than the bloodstream infections mediated by gram-negative and grampositive bacteria [79][80][81].…”
Section: Oral Mucosa As a Potential Source Of Candidemia By Candida Pmentioning
confidence: 99%